2021
DOI: 10.1088/1361-6528/ac40be
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Zeptomolar detection of 4-aminothiophenol by SERS using silver nanodendrites decorated with gold nanoparticles

Abstract: In the present work we report a simple, fast, reproducible and cheap methodology for SERS substrate fabrication of silver dendritic nanostructures (prepared by electrodeposition) decorated with gold nanospheres by electrophoretic deposition. This is the first report where a metal dendritic nanostructure has been decorated with another type of metal nanoparticles by this technique. The decorated nanostructures were used directly as SERS substrate using 4-aminothiophenol (4-ATP) as analyte. The objective of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The Raman peaks at 1014 and 1186 cm –1 are attributed to C–C bending vibration and C–H bending, respectively. The Raman peaks at 1500 cm –1 correspond to a combination of C–C stretching and C–H bending vibration . Finally, we chose a wavelength of 532 nm for the subsequent SERS tests.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Raman peaks at 1014 and 1186 cm –1 are attributed to C–C bending vibration and C–H bending, respectively. The Raman peaks at 1500 cm –1 correspond to a combination of C–C stretching and C–H bending vibration . Finally, we chose a wavelength of 532 nm for the subsequent SERS tests.…”
Section: Resultsmentioning
confidence: 99%
“…The Raman peaks at 1500 cm −1 correspond to a combination of C−C stretching and C−H bending vibration. 50 Finally, we chose a wavelength of 532 nm for the subsequent SERS tests. By comparison (Figure 1F), two dominant Raman peaks were observed at 1080 and 1591 cm −1 for Au/4-ATP, Au@Ag/4-ATP, and the nanoprobe compared to bare Au@Ag NPs, which are considered as characteristic peaks for 4-ATP.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…231−234 Yin et al have demonstrated the fabrication of Ag@Au core−shell dendrite structure on Si by synergetic hydrothermal corrosion and chemical reduction processes. 235,236 The fabricated structure illustrated the mean diameters of trunks, branches, and sub-branches of Ag@Au For example, Osminkina and co-workers have reported flowerlike gold NSs (AuNFs) on pSi/SiO 2 surface by one-spot synthesis for superior SERS detection. 238 The as-prepared AuNFs contained coral-like petals with 50−150 nm length, and the diameter was estimated to be ∼500 nm.…”
Section: Metal Nanodendrites Decorated On Si Substratementioning
confidence: 99%
“…Apart from AgNDs, highly branched gold NSs have drawn increasing attention to the area of sensing due to their promising optoelectronic properties for biomedical investigations. Yin et al have demonstrated the fabrication of Ag@Au core–shell dendrite structure on Si by synergetic hydrothermal corrosion and chemical reduction processes. , The fabricated structure illustrated the mean diameters of trunks, branches, and sub-branches of Ag@Au were about 120, 80, and 40 nm, respectively, with an average spacing of adjacent sub-branches of about ∼20 nm. The group tested SERS with widespread analytes like R6G, CV, methylene orange (MO), p -aminothiophenol (PATP), and DNA.…”
Section: Metal Nanodendrites Decorated On Si Substratementioning
confidence: 99%